Effects of triclabendazole and nitroxynil on EPG, hematological parameters and body weight against fascioliasis in goats at government goat development farm, Sylhet, Bangladesh (International Journal of Natural Sciences, 2016)
The study was conducted to evaluate the effects of triclabendazole and nitroxynil against fascioliasis in goat for a period of 28 days on 20 black bengal goats. Among hundred goats, twenty were selected for this study which was suffering from liver fluke (Fasciola gigantica) infection and were marked by tagging. Twenty goats were randomly divided into four groups (A, B, C and D) where each group comprising of five goats. Group A were treated with tablet fasinex (triclabendazole, Novartis Ltd, Bangladesh) orally at the dose rate of 12 mgkg-1body weight, group B were treated with acinex (triclabendazole, ACI Ltd, Bangladesh) orally at the dose rate of 12 mgkg-1body weight and group C were treated with nitronex injection (nitroxynil, Renata Ltd, Bangladesh) subcutaneously at the dose rate of 10 mgkg-1 body weight. Goats of group D was kept as infected control group without giving any treatment. A significant (P